Extreme dinosaurs - Mash, Robert, 1939-; Martin, Stuart (New York : Atheneum, 2008)
Profiles some of the most extreme dinosaurs, describing the world's smallest, largest, meanest, hungriest, and scariest dinosaurs to ever roam the earth.
6.6
3-6
Keywords: Dinosaurs -- Juvenile literature; Dinosaurs; Dinosaurs